Phase-Related Changes in the Sirtuin 1–High Mobility Group Box 1 Axis and Nicotinamide Adenine Dinucleotide in Ischemic Stroke - Bai, Lingling; Kang, Tao (Journal of Medical Biochemistry, 2026)
Background: This study investigated phase-related (acute, subacute, and recovery phases) changes in the peripheral blood sirtuin 1 (SIRT1)-high mobility group box 1 (HMGB1) axis after ischemic stroke (IS) and evaluated agreement between enzyme-linked immunosorbent assay and high-performance liquid chromatography for serum nicotinamide adenine dinucleotide (NAD+) measurement. Methods: Eighty patients with IS were classified as acute, subacute, or recovery phase according to time from onset, and 40 age- and sex-matched controls were included. Serum SIRT1, HMGB1, acetylated HMGB1, NAD+, interleukin-1 beta, tumor necrosis factor-alpha, and interleukin-10 were measured. Peripheral blood expression of SIRT1, HMGB1, inducible nitric oxide synthase, and arginase-1 messenger RNA was determined. Agreement for NAD+ measurement was assessed by Bland-Altman analysis. Results: In the acute phase, serum SIRT1 and NAD+ were lowest, whereas HMGB1, acetylated HMGB1, proinflammatory cytokines, and the inducible nitric oxide synthase/arginase-1 ratio were highest (P<0.05). Across the subacute and recovery phases, SIRT1 and NAD⁺ increased while HMGB1 and Ac-HMGB1 declined, with inflammatory balance indices trending toward control levels. Serum SIRT1 correlating negatively with FMA in the acute phase (r = −0.737) and positively in the recovery phase (r = 0.641). For NAD⁺ quantification, ELISA and HPLC demonstrated generally good agreement, with approximately 90% agreement in IS samples. Conclusions: Peripheral blood indices related to the SIRT1-HMGB1 axis show phase-dependent changes after IS and are accompanied by parallel changes in inflammatory status and motor function. Enzyme-linked immunosorbent assay showed acceptable agreement with high-performance liquid chromatography for serum NAD+ measurement.